The impact of smart mobility on household's travel behavior and residential self selection in a medium sized city in Nigeria - Aderibigbe, Oluwayemi-Oniya Bosede; Gumbo, Trynos (Frontiers in Sustainable Cities, 2025)
IntroductionUrban areas are widely recognized as key hubs of economic activity and cultural diversity, playing a vital role in both national and local economies. Improved mobility within cities has the potential to foster greater efficiency, environmental sustainability, and resource optimization, thereby promoting a more inclusive society. As a result, efforts to ensure fair access to transportation, housing, among others often necessitate policy reforms aimed at improving the mobility patterns of urban residents. Smart mobility involves transitioning from the conventional transportation systems and evolving toward mobility as a service, where intelligent infrastructure though the adoption of technology links multiple stakeholders and entities to provide an efficient, smart, and sustainable solution. This has found a niche in transportation policy, thus, impacting residential self-selection of households to live farther or closer to work and other non-work destinations such as parks, enclaves, shopping centers among others. Hence, this study examined the impact of smart mobility technologies on trip making behavior and housing choice of respondents.MethodsThis study adopted a rigorous research design, gathering primary data through the use of structured questionnaires. In total, 408 questionnaires was administered using a systematic sampling method, with the survey being conducted by research assistants. The Likert scale method for response ranking was utilized for ranking of factors influencing trip making behavior and housing choice of respondents, while the multiple regression analysis was used to validate the Likert scale results.DiscussionFindings indicated that the most significant factors (P < 0.05) influencing choice of residential location include proximity to work, transport cost, availability of public transport, good neighborhood and land/housing rent and telecommuting. Based on the above, it was discovered that the role of transportation in residential location choice plays a vital role in household's decision making, hence, improved mobility can lead to participative, and cohesive society.